Synthesis and Characterization of TiO2/CaTiO3 Perovskite Composite Derived from Pinctada maxima Shell Waste - Kurniawidi, Dian W.; Rahayu, Susi; Budianto, Arif; Saputra, Kormil; Agista, Wida Puteri; Suprayogi, Thatit; Marlina, Resti (Science and Technology Indonesia, 2025)
This study has succeeded in synthesizing and characterizing TiO2/CaTiO3 perovskite composites using calcium carbonate (CaCO3) from shellfish waste (Pinctada maxima). Synthesis was carried out through the coprecipitation method with variations in the molar ratio of CaCO3:TiO2 and calcination temperatures (700oC, 800oC, and 900oC). Characterization was carried out using FTIR, DTA-TG, XRD, SEM-EDS, BET and UV-Vis. The results of the analysis showed that the calcination temperature affected the powder color, crystal structure, thermal properties and particle size. The DTA-TG analysis shows that increasing the calcination temperature up to 900oC significantly reduces mass loss to 51.88%, with minimal thermal events, indicating the formation of a thermally stable and well-crystallized TiO2/CaTiO3 structure. At a temperature of 900oC, a more perfect CaTiO3 was formed with the whitest powder color, the anatase and brookite phases of TiO2 were still detected, while the calcite phase was still found at a temperature of 700oC. The morphology of the samples showed agglomeration with increasingly uniform particle sizes at higher calcination temperatures. Complementary BET analysis confirms that the composite possesses a mesoporous structure with a specific surface area of 11.42 m2/g and a pore size distribution of 3-5 nm, making it suitable for adsorption and photocatalytic applications. UV-Vis analysis showed an increase in the band gap value along with the increase in the TiO2 ratio. This is also confirmed by the presence of Urbach energy which tends to increase with increasing TiO2 ratio.